Kajian Batik Tradisi Bayat Klaten dengan Pendekatan Estetika - Aprilia Prastika; Sarwono Sarwono (Texture:Art and Culture Journal, 2022)
This research aims to describe the aesthetic according to Dharsono’s theory from 1) the look of a batik pattern visual on the main motif and the filling (isen), and 2) philosophical guidance on the motif related to  AgusSachari’s  aesthetic  theory  of  symbol,  meaning,  and  power  to  analyze  the  traditional  batik  in BayatKlaten. This is a qualitative descriptive research. Desa Jarum, Desa Kebon, and DesaBanyuripan in Bayat Sub-distric, Klaten, were chosen for the research locations. The research samples were collected using purposive sampling technique. The data sources consisted of informants, objects, pictures, archives, and  documents.  Data  triangulation  technique  was  utilized  to  validate  the  research  data.  The  analysis model used is the interactive analysis. The results show that the aesthetic of traditional batik according to Dharsono are: (1) The visual look of the batik’s main motif is the characteristic of the batik motif, the filling motif functions as an additional motif which has no meaning, and the filling (isen) acts as the filler on the blank space on the main and supporting motifs which are in the form of points and lines. 2) The philosophical guidance on the motif has symbol, meaning, and power related to AgusSachari’s aesthetic theory.